Measuring Happiness Behavior in Functional Analyses of Challenging Behavior for Children with Autism Spectrum Disorder. Issue 3 (May 2021) - Thomas, Benjamin R.; Charlop, Marjorie H.; Lim, Nataly; Gumaer, Caitlyn
This two-experiment study assessed the utility of measuring happiness behavior (e.g., smiling and/or laughing) within functional analyses (FA) of challenging behavior, and using results to inform interventions for children with autism spectrum disorder (ASD). In Exp. 1, we concurrently measured happiness behavior within the trial-based FA's of challenging behavior of four children with ASD. Results showed differentiation for both challenging behavior in test trials and happiness behavior within controls. In Exp. 2, we compared interventions based on challenging and happiness behavior from FA results for three of the participants, using a multiple-baseline across-participants design, with embedded reversals. Results suggested that interventions derived from measures of the children's happiness behavior led to reductions challenging behavior that were similar to interventions informed by challenging behavior, and were also associated with increased happiness behavior. Taken together, these two experiments suggest that the measurement of children's happiness behavior in FA of challenging behavior appears to be helpful in determining interventions for children with ASD.